Tools to Support Classroom Settings: Perceptions of EFL Students on ICT Usage during Pre-Service Teaching Program - Siti Munawaroh; Syahdan Syahdan (Utamax : Journal of Ultimate Research and Trends in Education, 2019)
ICT is used in the classroom context to help pre-service teacher or practicum teachers to know more learning materials beyond the textbooks. This study aims at investigating perceptions using ICT in the learning process during their pre-service teaching program. This survey research was taking EFL students at the English Education Department, Universitas Lancang Kuning, who conducted practice teaching or pre-service teaching at other schools in the province. Sixty-four students participated in this study. A set of questionnaires, with a Likert scale of 20 items and closed-ended five questions, was used to collect the data to ask their perception in ICT use during practice teaching at schools, the academic year 2019-2020. Some questionnaire items were adopted and developed from (Zare-ee 2011). The findings reveal that most pre-service teachers (90%) used ICT in the classroom. The analysis using statistical analysis (SPSS ver. 20), it was found that the mean score at 4.08 with a standard deviation value at 0.144 categorized High level. The score of standard deviation means that all of the respondents' answers are the same agree or homogenous. It means that pre-service teachers agree on the importance of using ICT in the classroom's learning process and acting as supportive tool to grasp meaningful English learning resources, especially in classroom settings.